Peran Pemerintah Kelurahan Kebonsari Surabaya dalam Pemberdayaan Usaha Mikro Kecil dan Menengah - Kinanti Resmi Hayati; Izzatun Nisak; Amalia Tasya Salsabila Suyanto; Mahesha Aginio Bimantio (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
The national economy has experienced economic growth this year. One of the driving factors for economic growth is the progress of MSMEs. The progress of MSMEs cannot be separated from the role of the government as an institution that oversees, guides, and encourages the smooth running of MSME activities in improving the national economy. This study aims to analyze the role of the village government in promoting the growth of MSMEs in Kebonsari Village. This study uses a qualitative research method with a descriptive type of approach. The data analysis technique using Gede Diva's theory of the government's role includes three indicators, namely: facilitator, regulator, and catalyst. Kebonsari Village has been quite active as a facilitator, catalyst, and regulator in supporting the development of SMEs in Kebonsari Village. The role of the village as a facilitator can be seen through its support for infrastructure and collaboration with outside parties. Kebonsari Village responds quickly to the complaints of Kebonsari SMEs. As a regulator, Kebonsari Village has implemented regulations or policies related to the empowerment of existing MSMEs to ensure legal certainty in the implementation of empowerment and improve the ability of microbusinesses to face business competition